2018
DOI: 10.1177/1359105318781935
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians’ moral distress and family satisfaction in the intensive care unit

Abstract: This study explored the relationship between clinicians' moral distress and family satisfaction with care in five intensive care units in Italy. A total of 122 clinicians (45 physicians and 77 nurses) and 59 family members completed the Italian Moral Distress Scale-Revised and the Family Satisfaction in the ICU questionnaire, respectively. Clinicians' moral distress inversely correlated with family satisfaction related to the inclusion in the decision-making process. Specifically, physicians' moral distress in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 43 publications
2
36
0
Order By: Relevance
“…Finally, the results of our study demonstrate that commitment to quality leadership, implementing quality improvement, and hand-off communication significantly predicted family members' satisfaction. This is in accordance with the findings in other studies where communication between the healthcare professionals and the patient and their family were shown to play a key role in patients' assessment of their hospitalization experience (Clark et al, 2016;Ferrando et al 2019;Hwang et al, 2014;Lam et al, 2015;Lamiani, Ciconali, Argentero, & Vegni, 2020;Schleyer & Curtis, 2013;van den Broek et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Finally, the results of our study demonstrate that commitment to quality leadership, implementing quality improvement, and hand-off communication significantly predicted family members' satisfaction. This is in accordance with the findings in other studies where communication between the healthcare professionals and the patient and their family were shown to play a key role in patients' assessment of their hospitalization experience (Clark et al, 2016;Ferrando et al 2019;Hwang et al, 2014;Lam et al, 2015;Lamiani, Ciconali, Argentero, & Vegni, 2020;Schleyer & Curtis, 2013;van den Broek et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, low perceived empowerment and autonomy represented vulnerability factors for MD. Concerning professional attitudes, low work satisfaction and engagement were associated with experiencing MD [60,61].…”
Section: Vulnerability Indicators For Moral Distress and Moral Injury In Healthcare Workersmentioning
confidence: 99%
“…In this context, lacking support from colleagues or supervisors [66]-represented as low professional [62] and social support [67]-posed vulnerability factors for MD [68]. Low informal and formal support may also be present in poor and unclear communication within the team [61] as well as in poor cooperation between different occupational groups of doctors, nurses, and students [5,61].…”
Section: Vulnerability Indicators For Moral Distress and Moral Injury In Healthcare Workersmentioning
confidence: 99%
“…Indeed, studies have shown that healthcare professionals are exposed to frequent conditions causing moral distress. For example, performing painful procedures or futile care, following physicians’ prescription or family wishes which are considered inconsistent with the patient’s good, perceiving unsafe or incompetent staffing [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%